Features of legal regulation of objects under construction - Омельченко, Ганна Василівна; Філатьєва, Наталія Віталіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
This article investigates scientific approaches of Ukrainian and Russian lawyers about interpretation the term "object under construction" and commissioning of such objects. Highlights the problems of legal regulation of entering and recognition the right of ownership. Analyze transactions that can be done with such objects